THE INLUENCE OF ACCOUNTING KNOWLEDGE AND PERSONALITY TOWARDS THE USE OF ACCOUNTING INFORMATION IN INVESTMENT DECISION MAKING - Djuwito Djuwito (Universitas Hayam Wuruk Perbanas, 2010)
The municipalities of Tanggulagin and Wedoro are considered the centre of the Small and Medium Enterprises (SME) in the regency of Sidoarjo. These two regencies have been prepared by the government of Sidoarjo and the province of East Java to become the centre of the SMEs to develop and go into global market. Yet, due to the uncertainty of the Lapindo mud explosion, the sale and marketing distribution of the products have been significantly influenced so that the economic growth also lowered down. The research method used in this research is quantitative approach using linear multiple regression which consists of independent variables of accounting knowledge (X1) and entrepreneur personality (X2) and the moderating variable of the environment uncertainty (X3). The dependent variable the accounting information and investment decision (Y). The results show the knowledge of accounting has no impact on the use of accounting information in making decision for investment, the entrepreneur personality, on the other hand, influences the use of accounting information in making decision for investment. Besides that, it is found that the environment uncertainty is, in fact, not the moderating variable. This variable does not moderate the knowledge of accounting and the entrepreneur personality by using the accounting information for making decision for investment.